KEANEKARAGAMAN IKAN PANTAI DI PULAU BANGKA - Eva Utami (Akuatik: Jurnal Sumberdaya Perairan, 2011)
Family Atherinidae was caught mostly by beach seine method. Persentage of individu was caught 51,98 % from all catch. Habitat of Atherinidae is in sandy beach and they usually do scholling. Spesies was mostly found in Bangka Island is Gerres oyena (Gerranidae). Dwelling of this spesies is in sandy beach. This research was done on sandy beach as habitat of Gerres oyena. Diversity index of this research is 1,155. It shows that diversity of fish are low. Seagrass was discoverd on seabed of research location partially. Seagrass have function as nursery and feeding ground by fish. So that fish can be assossiated on seagrass as its dwell. Part of seabed reseach location is sandy with a lesser amount of seagrass. It cause diversity of fish become low. Nevertheless, On 1st and 2nd research location, ship of tin mining and floating mining boat were operated. Both activity are suspended solid source on water. It initiates high turbidity